A micromechanical model for the transformation induced plasticity in polycrystalline steels. Issue 1 (21st October 2015) - Waimann, Johanna; Junker, Philipp; Hackl, Klaus
Abstract: Due to the effect of transformation induced plasticity (TRIP), TRIP‐steels are very promising materials, e.g. for the automobile industry. The material behavior is characterized by very complex inner processes, namely phase transformation coupled with plastic deformation and kinematic hardening. We establish a micromechanical model which uses the volume fractions of the single phases, the plastic strain and the hardening parameter in every grain of the polycrystalline material as internal variables. Furthermore, we apply the Principle of the Minimum of the Dissipation Potential to derive the associated evolution equations. The use of a coupled dissipation functional and a combined Voigt/Reuss bound directly results in coupled evolution equations for the internal variables and in one combined yield function. Additionally, we show numerical results which prove our model's ability to give a first prediction of the TRIP‐steels' complex material behavior. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)